GAME ACTIVITIES IN THE TRAINING SYSTEM STUDENTS OF HIGHER PEDAGOGICAL INSTITUTIONS FOREIGN COMMUNICATION - L.P. Haponenko (Academy of Cognitive and Natural Sciences, 2004)
The article shows the essence of the students' playing activity during their foreign language communication training. The author gives the examples o f using some kinds of games in practice and demonstrates the effectiveness of using playing activities of students as prospective teachers in order to prepare them to foreign communication.